Meningkatkan Keberlanjutan Pertanian Sayuran dengan Rotasi Tanaman dan Green Marketing - Rosita, Rosita; Oktanisa, Silvana; Febrianni, Astri; Rismarini, Rismarini; Munparidi, Munparidi; Cathabella, Tarishah; Nurrizqi, Edvantika Merbasayu; Adinda, Dwike Marsyah (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
The women's farmer group (KWT) in Lalang Sembawa Village is engaged in vegetable farming. This KWT faces several challenges in marketing and growing a variety of vegetables on relatively limited land. This community service program aims to provide training on Green Marketing and demonstrate crop rotation to improve the sustainability of vegetable cultivation. The approaches used in this community service include field observation, demonstrations, and presentations. The results of this community service program are increased knowledge about Green Marketing and the ability to implement vegetable crop rotation in the Pinang Merah KWT in Lalang Sembawa Village.